Reappraisal of Immotthia in Dictyosporiaceae, Pleosporales: Introducing Immotthia bambusae sp. nov. and Pseudocyclothyriella clematidis comb. et gen. nov. Based on Morphology and Phylogeny - Jiang, Hong-Bo; Jeewon, Rajesh; Karunarathna, Samantha C.; Phukhamsakda, Chayanard; Doilom, Mingkwan; Kakumyan, Pattana; Suwannarach, Nakarin; Phookamsak, Rungtiwa; Lumyong, Saisamorn (Frontiers in Microbiology, 2021)
Immotthia is a poorly known genus and currently no DNA sequence data available to ascertain its proper phylogenetic placement and evolutionary relationships with other bitunicate fungi. To date, there are only two species accepted in the genus. During our ongoing research study of bambusicolous fungi in southwest China and Thailand, a fungus associated with stromata of Hypoxylon sp. was found on dead bamboo culms in Loei Province, Thailand. Preliminary morphological identification revealed that the fungal collection belongs to Immotthia. A novel species, Immotthia bambusae, is introduced herein based on a comparison of morphological characteristics with the type specimen of I. hypoxylon (≡ Amphisphaeria hypoxylon Ellis & Everh.), a synonym of I. atrograna (Cooke & Ellis) M.E. Barr. Phylogenetic analyses of a concatenated ITS, LSU, SSU and TEF1-α DNA sequence matrix showed that Immotthia belongs to Dictyosporiaceae, Pleosporales. Despite Immotthia bambusae strains constitute a supported subclade, they are nested with the genus Pseudocoleophoma. Pseudocoleophoma clematidis is morphologically different from all other Pseudocoleophoma species while its conidial characteristics are similar to Cyclothyrium. Multi-gene phylogenetic analyses showed that Pseudocoleophoma clematidis formed a clade basal to Immotthia, separated from Pseudocoleophoma with strong statistical support. Therefore, we introduce a monotypic genus, Pseudocyclothyriella Phukhams. & Phookamsak, gen. nov. to accommodate the single species, Pseudocyclothyriella clematidis (Phukhams. & K.D. Hyde) Phukhams. & Phookamsak, comb. nov. Detailed descriptions, color micrographs and phylogenetic trees to show the placement of the new taxa are provided. In addition, an updated taxonomic treatment of the genera Immotthia and Pseudocyclothyriella are also provided based on study of the type materials and phylogeny generated from DNA sequence data.